2020
DOI: 10.1177/0020764020903334
|View full text |Cite
|
Sign up to set email alerts
|

Indonesian online newspaper reporting of suicidal behavior: Compliance with World Health Organization media guidelines

Abstract: Background: Despite the lack of attention, suicide is a major public and mental health problem in Indonesia. Research on how Indonesian newspapers portray suicide case has been lacking. Aim: To assess the quality of Indonesian online newspaper reporting suicide news and its compliance with the World Health Organization (WHO) mass media reporting guidelines. Methods: The content of suicide news reported in online newspapers was searched and scrutinized against the WHO suicide reporting guidelines. Results: With… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 19 publications
8
27
0
Order By: Relevance
“…Consistent with our findings, studies from other Asian countries, such as Bangladesh (Arafat et al, 2019; Arafat, Khan, et al, 2020), Indonesia (Nisa et al, 2020), Bhutan (Zangmo & Zangmo, 2019), Pakistan (Kamboh & Ittefaq, 2019), Sri Lanka (Brandt Sørensen et al, 2019) and China (Chu et al, 2018), have also noted several breaches in media reporting such as the inclusion of identifying characteristics such as age, gender and occupation of the victim coupled with graphical illustrations and explicit details about the methods, steps involved in suicide and descriptions about the suicide note. Put together, these findings indicate that the adherence to media reporting guidelines in Asia is low and the quality of reporting is poor.…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with our findings, studies from other Asian countries, such as Bangladesh (Arafat et al, 2019; Arafat, Khan, et al, 2020), Indonesia (Nisa et al, 2020), Bhutan (Zangmo & Zangmo, 2019), Pakistan (Kamboh & Ittefaq, 2019), Sri Lanka (Brandt Sørensen et al, 2019) and China (Chu et al, 2018), have also noted several breaches in media reporting such as the inclusion of identifying characteristics such as age, gender and occupation of the victim coupled with graphical illustrations and explicit details about the methods, steps involved in suicide and descriptions about the suicide note. Put together, these findings indicate that the adherence to media reporting guidelines in Asia is low and the quality of reporting is poor.…”
Section: Discussionsupporting
confidence: 92%
“…The present study shows that, generally, the media reporting of suicidal behaviour in Ghana does not comply with the WHO reporting guidelines. This evidence supports recent findings from other LAMICs in Asia, including Bangladesh, Bhutan, India, Indonesia, Sri Lanka and Taiwan (Arafat et al, 2019;Chiang et al, 2016;Nisa et al, 2020;Sørensen et al, 2019;Zangmo & Zangmo, 2019). The evidence also supports a previous anecdotal observation that media coverage of suicide in Ghana is sensational, overly simplistic and explicit (Quarshie et al, 2015).…”
Section: Discussionsupporting
confidence: 91%
“…details of suicide method) is common, while recommended helpful reporting practices are scarce -for example, providing contact details of available and accessible suicide support services (Armstrong et al, 2018;Chandra et al, 2014). In Bangladesh, Bhutan, China, India, Indonesia, Korea, Sri Lanka and Taiwan, both online and newspaper reporting of suicide have been found to fail in adhering to the WHO recommended reporting guidelines (Arafat et al, 2019;Chandra et al, 2014;Chang & Freedman, 2018;Chu et al, 2018;Chun et al, 2018;Nisa et al, 2020;Sørensen et al, 2019;Zangmo & Zangmo, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The high frequency of harmful reporting characteristics observed in the present study is consistent with the low adherence to WHO guidelines reported in other neighbouring Asian countries as well ( Arafat et al, 2020a ). Studies from Bangladesh ( Arafat et al, 2020b ), Indonesia ( Nisa et al, 2020 ) and Sri Lanka ( Brandt Sørensen et al, 2019 ) have also reported non-adherence to WHO recommendations in print media such as reporting of suicide method, description of suicide note and inclusion of personal identification characteristics in reports. The headlines of the online reports included in the current study used the term ‘suicide’ in 18 % articles.…”
Section: Discussionmentioning
confidence: 99%